2015
DOI: 10.1038/nmat4298
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-crystalline ordering of antimicrobial peptide–DNA complexes controls TLR9 activation

Abstract: Double-stranded DNA (dsDNA) can trigger the production of type I interferon (IFN) in plasmacytoid dendritic cells (pDCs) by binding to endosomal Toll-like receptor-9 (TLR9; refs 1-5). It is also known that the formation of DNA-antimicrobial peptide complexes can lead to autoimmune diseases via amplification of pDC activation. Here, by combining X-ray scattering, computer simulations, microscopy and measurements of pDC IFN production, we demonstrate that a broad range of antimicrobial peptides and other cationi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(152 citation statements)
references
References 24 publications
7
145
0
Order By: Relevance
“…Of the previously described responses, macrophage activation by DNA-CATH-2 complexes appears to be most similar to B cell activation by DNA-LL-37 complexes (30), which also respond by upregulation of proinflammatory cytokines, such as IL-6, whereas reported responses of monocytes and pDCs are limited to enhanced type I IFN production (18,25,31), which was unaffected in our study. Interestingly, although many cathelicidins were able to enhance DNAinduced activation in chicken macrophages, increasing DNA uptake might not be the only way by which they can enhance endosomal TLR activation (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Of the previously described responses, macrophage activation by DNA-CATH-2 complexes appears to be most similar to B cell activation by DNA-LL-37 complexes (30), which also respond by upregulation of proinflammatory cytokines, such as IL-6, whereas reported responses of monocytes and pDCs are limited to enhanced type I IFN production (18,25,31), which was unaffected in our study. Interestingly, although many cathelicidins were able to enhance DNAinduced activation in chicken macrophages, increasing DNA uptake might not be the only way by which they can enhance endosomal TLR activation (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the immunoreactivity of CpG ODN changes depending upon its formation of complexes with proteins (or peptides) or nanoparticles, [29][30][31] and ODNs without CpG can be made recognizable to TLR9. 32,33 These findings enable a broad range of research strategies for CpG ODN nanomedicines.…”
Section: Introductionmentioning
confidence: 95%
“…32 This type of TLR9-mediated IFN-α induction, independent of CpG, was also observed in complexes of double-stranded natural phosphodiester DNA and human β-defensin-3 or penetratin, but it was not observed in complexes with Tat-derived peptides. 33 Small-angle X-ray scattering measurements showed that the DNA is organized into a columnar arrangement within all complexes. However, in complexes that induce IFN-α, the first diffraction peak appears at 1.8-2 nm -1 , compared with the first peak position at 2.48 nm -1 for Tat-derived peptides and DNA complexes.…”
mentioning
confidence: 99%
“…Another is the fast advancing field of nanoparticles as anti-viral drugs, [147][148][149][150] where multivalent particles are used that mimic, and compete with, cell receptors. Both these applications can benefit from the same approaches and techniques used to understand targeting selectivity, [70][71][72]79 and indeed some initial step in that direction have already been taken. 147,[151][152][153] In general, the take-home message that we would like to deliver is that a deeper integration of theory and computational modelling in the design stage of specific system would be welcome.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently this strategy has not had much success, for which various reasons have been brought forward. 68 Whereas it is widely thought that problems, such as immunogenicity are chemistry dependent and might be difficult to study using the kind of coarse-grained models we discuss here (although some recent results are starting to question this assumption 70 ), other aspects of selectivity can well be captured within this modelling approach. In fact, selective targeting via functionalised nanoparticles is an area where modelling has predicted very interesting and sometimes counter-intuitive behaviours, [71][72][73] whose exploitation might be extremely useful in the design of targeting systems, as we are about to discuss.…”
Section: Controlling Nanoparticles Binding Selectivitymentioning
confidence: 99%